2013
DOI: 10.1103/physrevlett.110.214503
|View full text |Cite
|
Sign up to set email alerts
|

Ship Wakes: Kelvin or Mach Angle?

Abstract: From the analysis of a set of airborne images of ship wakes, we show that the wake angles decrease as U −1 at large velocities, in a way similar to the Mach cone for supersonic airplanes. This previously unnoticed Mach-like regime is in contradiction with the celebrated Kelvin prediction of a constant angle of 19.47 o independent of the ship's speed. We propose here a model, confirmed by numerical simulations, in which the finite size of the disturbance explains this transition between the Kelvin and Mach regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
140
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 15 publications
14
140
1
1
Order By: Relevance
“…We plot the Mach angle line 4.52 ⁄ with the coefficient 4.52 adopted from the wave pattern when the particle's velocity is 0.9c. The results show clearly the transition from Kelvin angle of 19.5° at small velocities of the charged particle to the Mach angle at large velocities, being similar to the recent studies in fluid mechanics [26,27].…”
supporting
confidence: 90%
“…We plot the Mach angle line 4.52 ⁄ with the coefficient 4.52 adopted from the wave pattern when the particle's velocity is 0.9c. The results show clearly the transition from Kelvin angle of 19.5° at small velocities of the charged particle to the Mach angle at large velocities, being similar to the recent studies in fluid mechanics [26,27].…”
supporting
confidence: 90%
“…In some surveys manta net was fixed from the stern of the vessel 17,18 , but in that case you have to be sure that the net is out of the wake zone. The distance, on which the trawl is set for sampling, should be determined individually, since the zone of turbulences caused by the vessel varies from the size of the vessel and from the speed of the boat 19,20 . Separation of microplastic particles from the sea surface samples is most often done just by visual identification 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research (Rabaud & Moisy 2013;Darmon et al 2014) has highlighted the complexity of the ship wake structure and demonstrated that the appearance and properties of even the (formally) Kelvin wake may substantially change at higher Froude numbers. Our analysis shows that remarkable differences of the actual wake patterns from the ideal linear Kelvin wakes exist even at relatively low Froude numbers.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…An increase in the ship speed is, most probably, associated with an increase in the proportion of non-stationary components of the wave wake, and consequently, a widening of the frequency spectrum of the wake. A series of recent studies has also been devoted to the investigation of wake patterns for length Froude numbers F L 0.5, for which recent observations have highlighted that the dominant wake wedge angle is 232 T. Torsvik, T. Soomere, I. Didenkulova and A. Sheremet significantly less than the Kelvin angle, and that the angle decreases with increasing ship speed (Rabaud & Moisy 2013). However, these observations are not necessarily in contradiction with linear Kelvin wake theory (Darmon, Benzaquen & Raphael 2014;Noblesse et al 2014), but indicate that the highest waves may not coincide with the cusp line wave system for ships sailing in the high Froude number regime, making it difficult to determine the actual edge of the wake wedge.…”
mentioning
confidence: 99%